Phytochemistry and hemostatic properties of some medicinal plants sold as anti-hemorrhagic in Cotonou markets (Benin) - Dandjesso, C.; Klotoé, JR.; Dougnon, TV.; Sègbo, J.; Atègbo, J-M.; Gbaguidi, A. Fernand; Fah, L.; Fanou, B.; Loko, F.; Dramane, K. (My University, 2012)
Annona senegalensis (Leaves), Newbouldia laevis (Leaves), Cassytha filiformis (aerial part), Cissampelos mucronata (aerial part) are four species of medicinal plants commonly sold by herbalists in South Benin for treatment of bleeding. Hemostatic tests performed in vitro on hydro alcoholic extracts of these plants revealed that all of them have coagulant properties, with a percentage reduction of plasma re-calcification time which is 31% for C. filiformis and 39% for A. senegalensis. The action of these plant extracts is different from that of the classical pathway of blood coagulation. A. senegalensis extract also showed an astringent power. The phytochemical study of these plants revealed that: C. mucronata contains alkaloids and tannins; A. senegalensis contains tannins, mucilages and reducing compounds; C. filiformis contains alkaloids, tannins (gallic tannins and cathetics) and mucilage; N. leavis contains tannins, triterpenoids, mucilages and reducing compounds. The traditional use of plants as hemostatic is convicted with these results.
Keywords: Astringent; Hemostatic tests; Herbal; Medicinal plants